2005
DOI: 10.1534/genetics.105.042564
|View full text |Cite
|
Sign up to set email alerts
|

Repeat-Induced Point Mutation and the Population Structure of Transposable Elements in Microbotryum violaceum

Abstract: Repeat-induced point mutation (RIP) is a genome defense in fungi that hypermutates repetitive DNA and is suggested to limit the accumulation of transposable elements. The genome of Microbotryum violaceum has a high density of transposable elements compared to other fungi, but there is also evidence of RIP activity. This is the first report of RIP in a basidiomycete and was obtained by sequencing multiple copies of the integrase gene of a copia-type transposable element and the helicase gene of a Helitron-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 55 publications
4
73
1
1
Order By: Relevance
“…In this study, analysis of homologous TEs clearly revealed that U. hordei employs RIP to control TE activity: Numerous point mutations representing C-to-T (G-to-A) transitions were discovered when similar TEs were aligned (see Supplemental Figure 6 online). Many occurred at TCG triplets (or CGA on the opposite strand) as found in a related smut fungus Microbotryum violaceum (Hood et al, 2005), though they were not strictly limited to these triplets as in M. violaceum. This could point to a more complex RIP mechanism than found to date in ascomycetes (Clutterbuck, 2011) or indicate a different mechanism.…”
Section: Genome Defenses Related To Te Control and Heterochromatin Fomentioning
confidence: 91%
“…In this study, analysis of homologous TEs clearly revealed that U. hordei employs RIP to control TE activity: Numerous point mutations representing C-to-T (G-to-A) transitions were discovered when similar TEs were aligned (see Supplemental Figure 6 online). Many occurred at TCG triplets (or CGA on the opposite strand) as found in a related smut fungus Microbotryum violaceum (Hood et al, 2005), though they were not strictly limited to these triplets as in M. violaceum. This could point to a more complex RIP mechanism than found to date in ascomycetes (Clutterbuck, 2011) or indicate a different mechanism.…”
Section: Genome Defenses Related To Te Control and Heterochromatin Fomentioning
confidence: 91%
“…Secondly, this situation could be realized in other biological processes that may require the pairing of identical sequences, for instance, repeat induced point mutation. 45,46 To probe how the homologous segments recognize each other, we shift the centre of fragment 2 a distance x along the z-axis. Therefore, the centre of fragment 1 lies at z = L/2, whereas that of fragment 2 lies at z = L/2 + x.…”
Section: A General Considerationsmentioning
confidence: 99%
“…In the case of Microbotryum, these include many transposable elements in its genome. Comparative study of the coevolution of transposable elements with fungal genomic defences (repeat induced point mutations; Hood et al, 2005) is another exciting future research area.…”
Section: Biotic Interactions: Microbotryum and The Evolutionary Ecolomentioning
confidence: 99%